Contested genre: locating US fantasy television in genre discourses - O'Dette, Katarina (2023)
Over the past two decades, fantasy has gone from an intermittent presence on United States television screens to one of its most popular genres. Despite this prevalence, there remains a persistent gap in the literature surrounding research on the televisual fantasy genre, with researchers claiming that the notoriously nebulous boundaries of fantasy complicate or even invalidate its study. This thesis argues that this contestation is in fact a core component, not just of fantasy, but of genre itself. Rather than considering genre a textual construct, I follow on from Jason Mittell’s work to view genre primarily as a cultural construct that is expressed discursively. The thesis conceives of different groups within the US television industry as genre stakeholders, each with their own investment in the idea of genre more generally and fantasy specifically. Through their discourses, these stakeholders express differing definitions and impressions based on their unique investments in a particular genre, creating, responding to, and perpetuating the impact of contestation.